Meta Analisis: Analisis Risiko Kesling Akibat Pajanan Karbon Monoksida (Co) Pada Pedagang - Nanda Bagus Wibisono; Eko Suhartono; Nelly Al Audhah; Muhammad Abdan Shadiqi; Nopi Stiyati Prihartini (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin, 2025)
Based on data released by GAHP in 2019, Indonesia is the fourth country with the highest death rate from pollution in the world. Based on data from the Health Research and Development Agency (Balitbangkes), the prevalence of ARI in South Kalimantan in 2018 was 27.1%. This prevalence is the 10th highest in South Kalimantan. Terminal Km 6, located in Banjarmasin, is one of the centres of commercial and transportation activities in the South Kalimantan region. Pollution in this area comes from the activities of traders and visitors, ranging from cigarette smoke, cooking aromas, to vehicle emissions. The general objective of this study was to review and analyse articles that explain the relationship between environmental health risks due to CO exposure in traders. The research design used was systematic literature review (SLR) with meta-analysis research type. Based on the literature search guided by the inclusion criteria and the selection process, 14 primary studies will be included in the data analysis stage and interpreted the results of the analysis. Primary studies obtained through the literature search stage guided by the inclusion criteria and through the study selection process totalled 14 primary studies. These studies were searched in several electronic databases. Selection of primary studies is an important step to ensure the eligibility of studies to be included in the meta-analysis so that the findings can be valid and reliable.